КОМПЕТЕНЦИЯВИЙ ЁНДАШУВ АСОСИДА БЎЛАЖАК МАТЕМАТИКА ЎҚИТУВЧИЛАРИНИ ТАЙЁРЛАШ - Мамутова, Г.Ш. (SCIENCE and SOCIETY, 2019)
The article presents an overview of the development process of the future teacher of Mathematics based on the competence approach, the main requirements to their competence, the prospects of interactive methods in forming and developing the professional competence of the modern teacher of Mathematics.